2003
DOI: 10.1046/j.1528-1157.2003.41102.x
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Calcium Current Function on Heterotopic Neurons in Hippocampal Slices from Rats Exposed to Methylazoxymethanol

Abstract: Summary:Purpose: To study voltage-dependent calcium currents (VDCCs) on hippocampal heterotopic neurons by using whole-cell patch-clamp techniques in brain slices prepared from methylaxozymethanol (MAM)-exposed rats.Methods: Whole-cell voltage-clamp recordings were obtained from visually identified neurons in acute brain slices by using an infrared differential interference contrast (IR-DIC) video microscopy system. Heterotopic neurons were compared with normotopic pyramidal cells in hippocampal slices from MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Additional evidence points to trauma and infectious diseases during pregnancy contributing to human cortical dysplasia (Marin Padilla 1999;Deukmedjian et al 2004). Typical findings in human malformation disorders include altered excitability and disturbances in GABAergic mechanisms (Di Luca et al 1994;Ross 2002;Calcagnotto and Baraban 2003;Gardoni et al 2003;Bast et al 2004;Deukmedjian et al 2004;Levitt et al 2004 ). Our study shows that in a ferret model of cortical dysplasia, cortical cues are essential to proper migration and positioning of interneurons arising from the GE.…”
Section: Discussionsupporting
confidence: 53%
“…Additional evidence points to trauma and infectious diseases during pregnancy contributing to human cortical dysplasia (Marin Padilla 1999;Deukmedjian et al 2004). Typical findings in human malformation disorders include altered excitability and disturbances in GABAergic mechanisms (Di Luca et al 1994;Ross 2002;Calcagnotto and Baraban 2003;Gardoni et al 2003;Bast et al 2004;Deukmedjian et al 2004;Levitt et al 2004 ). Our study shows that in a ferret model of cortical dysplasia, cortical cues are essential to proper migration and positioning of interneurons arising from the GE.…”
Section: Discussionsupporting
confidence: 53%
“…We found that NMDA receptors did not mediate PE-induced inhibition of eEPSCs. A few studies reported that activation of ␣ 1 -adrenoreceptors can attenuate Ca 2ϩ currents (Calcagnotto and Baraban, 2003;Li and van den Pol, 2005). Since release of neurotransmitters relies on presynaptic Ca 2ϩ entry, this may explain PE-mediated inhibition on EPSCs in our preparation.…”
Section: Discussionmentioning
confidence: 76%
“…Battaglia et al, 2003a,b;Flagstad et al, 2005;Flagstad et al, 2004;Lavin et al, 2005;Lu et al, 2000). Even if several reports, including the majority of those addressing the altered neuronal excitability (Calcagnotto et al, 2002, Calcagnotto andBaraban, 2003;Castro et al, 2002) in MAM animals, have used a single injection approach with higher MAM doses, presumably leading to lower and less persistent levels of the toxic period, our data apply to both procedures of MAM treatment. Furthermore, studies support our conclusions, including those demonstrating a clear-cut interdependence of the cerebrovasculature with neuronal malformations and adult neurogenesis (Bardosi et al, 1985a,b;Bardosi et al, 1987;Palmer et al, 2000).…”
Section: Discussionmentioning
confidence: 87%